2021
DOI: 10.1177/09579265211048704
|View full text |Cite
|
Sign up to set email alerts
|

The slanted beam: A critical discourse analysis of anti-Islam and anti-Muslim discourse in China

Abstract: Adopting the Critical Discourse Analysis perspective, this study investigates the ideology reflected by the anti-Islam and anti-Muslim discourse in China, the power dynamics revealed by such discourse and how social media discourse differs from and utilises the government discourse. Four ways to disguise the anti-Muslims, anti-Islam prejudice are investigated: appealing to patriotism to demand cultural assimilation; claiming to defend secularism; framing Islam as incompatible with mainstream culture; appealing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Furthermore, Pilkington and Acik (2020) found that lack of individual recognition and inequality of young Muslims created social activism among them. Lan and Navera's (2022) study in China revealed that social media discourse and government discourse frame Islam as incompatible with mainstream culture and the patriotism demanded for assimilation into the main culture.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Pilkington and Acik (2020) found that lack of individual recognition and inequality of young Muslims created social activism among them. Lan and Navera's (2022) study in China revealed that social media discourse and government discourse frame Islam as incompatible with mainstream culture and the patriotism demanded for assimilation into the main culture.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Lan and Navera (2022) pointed out that in social media, the relationship between the interlocutor and the audience is rarely unidirectional, and upon the reception of the message, the audience may then re-produce the discourse (Shah et al, 2020). This condition also makes the abundance of information in social media often misleading, especially because everyone can give their opinion, regardless of their background and understanding rate of the issue.…”
Section: Misleading Information In Social Media and Responses From Th...mentioning
confidence: 99%
“…Tyto tematické celky byly také součástí zadání pro hloubkové rozhovory, pokud se k nim respondent během svého vyprávění nedostal, sloužily pak otázky v rámci těchto tematických celků pro doplnění chybějících informací. (Lan & Navera, 2022), tedy aby bylo možné zkoumat postoj a vnímání role vyučujících (Zábrodská & Petrjánošová, 2013). V tomto případě se jednalo o analýzu očekávání respondentů od vyučujících a vnímání jejich role při akademické integraci.…”
Section: Obrázekunclassified